Corporate governance practices in the family and ownership dimensions its impact on performance and socioemotional wealth (2016)
This paper analyzes the governance practices in the dimension of the family and ownership, and its impact in the financial and family performance. From an empirical perspective, we provide a exploratory evidence on how the governance practice in the structures of governance in the family and ownership, impacts in the financial results and the socioemotional wealth of the family.The results show that the implementation of corporate governance practices in the family and ownership dimensions is not a reliable indicator of a direct relationship with business performance. In addition, we found strong tendencies to preserve the family’s socioemotional wealth. Furthermore, unity, honesty, transparency and amity are factors boosting both family and business success.This study has some limitations, the qualitative method used, such as the case study, allows an analytic exploration of the findings. However, it would be suitable further future quantitive approaches to generalize our results and extract more objective conclusions